2012
DOI: 10.2139/ssrn.2112035
|View full text |Cite
|
Sign up to set email alerts
|

Is Financial Fragility a Matter of Illiquidity? An Appraisal for Italian Households

Abstract: In this paper we investigate household financial fragility and assess the role played by the composition of the household portfolio besides standard determinants of this condition (e.g. income, indebtedness, age, gender, financial literacy). We take the case of Italy, given the very peculiar portfolio composition (high level of housing and low level of indebtedness and portfolio diversification) and provide two main contributions. First, we propose a novel definition of financial fragility. Second, based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 24 publications
1
34
2
Order By: Relevance
“…The same indicator is used in Brunetti et al . () to analyse whether excessive portfolio illiquidity due to homeownership is connected to financial fragility of Italian households . Moreover, we consider separately the presence of a mortgage using a dummy (and for this reason we do not consider net wealth).…”
Section: Econometric Specifications and Resultsmentioning
confidence: 99%
“…The same indicator is used in Brunetti et al . () to analyse whether excessive portfolio illiquidity due to homeownership is connected to financial fragility of Italian households . Moreover, we consider separately the presence of a mortgage using a dummy (and for this reason we do not consider net wealth).…”
Section: Econometric Specifications and Resultsmentioning
confidence: 99%
“…However, Brunetti, Giarda & Torricelli (2012) reported that males were more likely to experience financial fragility. However, Del Rio and Young (2005) and Loke (2016) found no gender difference in self-assessed financial burdens and living beyond ones means, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…should not be confused with financial literacy, which had a recognisable value in managing debt (Nyaruwata, 2009;Brunetti et al, 2012;Loke, 2016). Lack of financial education is a key determinant of over-indebtedness (Disney & Gathergood, 2011;Cavalletti, Lagazio, Vandone & Lagomarsino, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent work has been aided by the arrival of more detailed data on household balance sheets ), Lusardi (2011), Jappelli et al (2013, Ampudia et al (2016), Brunetti et al (2016)) and aims to gauge borrowing capacity and resilience to sudden, unforeseen expenditures. Specifically, this work primarily focuses on measuring the ability of households to remain current on incurred debts, as well as the question of how much borrowing the household could feasibly engage in, within a short term period, e.g., 30 daysespecially to cover an unforeseen "expense" (as opposed to a change in income, say).…”
Section: Related Workmentioning
confidence: 99%